2018
DOI: 10.1038/s41598-018-34361-3
|View full text |Cite
|
Sign up to set email alerts
|

Disease networks identify specific conditions and pleiotropy influencing multimorbidity in the general population

Abstract: Multimorbidity is an emerging topic in public health policy because of its increasing prevalence and socio-economic impact. However, the age- and gender-dependent trends of disease associations at fine resolution, and the underlying genetic factors, remain incompletely understood. Here, by analyzing disease networks from electronic medical records of primary health care, we identify key conditions and shared genetic factors influencing multimorbidity. Three types of diseases are outlined: “central”, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 82 publications
2
24
0
Order By: Relevance
“…Cholecystitis/cholelithiasis and cataract have also a high degree (6 th and 7 th position out of 148) in the general network. The causal genes of central diseases, with a major impact on multimorbidity, have the potential to influence multiple diseases 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystitis/cholelithiasis and cataract have also a high degree (6 th and 7 th position out of 148) in the general network. The causal genes of central diseases, with a major impact on multimorbidity, have the potential to influence multiple diseases 52 .…”
Section: Discussionmentioning
confidence: 99%
“…This section describes the proposed Hierarchical Agglomerative Clustering for cooccurrence analysis, denoted HAC-cooc, which clusters the blocks of diagnoses [23,24]. The algorithm constructs a clustering solution by first considering each diagnosis block as a cluster and then by iteratively agglomerating pairs of diagnosis clusters using a local rule based on the maximization of the RR measure.…”
Section: The Hac-cooc Algorithmmentioning
confidence: 99%
“…The literature on multimorbidity patterns was reviewed in 2014 by Pradros-Torres et al and in 2019 by Busija et al, and several methods and population contexts were identified [16,17]. The methods were factor analysis, to discover underlying common factors of diseases [18,19]; clustering analysis, to regroup either diseases or people into clusters [20][21][22]; or network analysis, to study the links between pairs of diseases [23]. These approaches are mainly focused on disease analysis of complex and chronic patients, which represent the greatest burden on the healthcare economy.…”
Section: Introductionmentioning
confidence: 99%
“…Amell et al used network analysis to find age and gender-related trends in disease association. 25 They were also able to indicate diseases with low cumulative risk, which still inform continued disease clustering, and pleiotropy (two or more unrelated effects in the production of a single disease) influencing multimorbidity. Miles et al contend that multimorbidities occur when stressors from an individual's physical and sociocultural environment provoke maladaptive responses in more than one of the body's numerous interconnected physiological networks, thus resulting in interrelated pathologies and chronic conditions.…”
mentioning
confidence: 99%
“…28 Despite the strong causal connections between weight increase and comorbidity, most previous studies have only assessed static comorbidity patterns and differences in the prevalence and interactions of comorbidities by age and gender. 23,25 What is already known about this subject?…”
mentioning
confidence: 99%